Stress state analysis and symmetrical optimization of double-row non-symmetrical arrangement of anchorage slot in concrete lining structure - Chun-E. Sui; Chengcheng Shi; Jingfu Kang; Wenjun Yang; Dan Qiao; Qi Guo (Case Studies in Construction Materials, 2024)
The role of the anchorage slot is to fix the anchorage and tension anchor rope, which is the weakest link of the concrete lining structure. The stress state of the anchorage slot area in the construction and operation stages of the 2# sand discharge of the Xiaolangdi Project was analyzed by modeling in this paper. The results showed that the stress state of the anchorage slot area was the most complex. The tensile stress was generated in the radial direction of the concrete lining during the construction period, and the circumferential pre-compression stress was unevenly distributed along the thickness direction. During the operation period, when the backfill concrete at the anchor slot and the lining jointly bore the internal water pressure, a tensile stress of 0.89 MPa was generated in the inner anchorage slot area of the lining, which was less than the tensile strength of the concrete itself. Finite element calculation results were compared with the field-measured data, and the results were essentially the same. Finite element analysis software was used to optimize the double-row asymmetric arrangement of the anchorage slots into a single-row symmetrical structure. The results showed that the angle of the complex stress area of the lining is reduced by about 75%. The optimized single-row symmetrical anchorage slot layout was safer, and the pre-stressing distribution was more uniform.